Students' Needs Analysis: Teaching Palembang Local Culture Procedure Text with Android for Hospitality Industry Program - Wahyuni, Ummy; Eryansyah, Eryansyah; Inderawati, Rita (Celt: A Journal of Culture, English Language Teaching & Literature, 2022)
The globalization period is characterized by rapid advances in research, especially in the field of technology. Learning in social contexts and virtual learning must be taken into account to keep up with the needs of the industry era 4.0. With the help of SMK students and teachers, this study attempts to find out the students' needs in Procedure text reading material based on local culture in Palembang. The writer utilized a questionnaire and an interview to gather information. Statistics and qualitative analysis of the data were conducted. The need revealed that: 1) English was required for the students to help them in their future careers, and 2) English language proficiency of the students was still at the preliminary level, 3) the students' interest in reading was low, 4) the topic related to general knowledge was relevant, 5) The local culture of Palembang was crucial as a topic in reading comprehension, 6) The type of texts needed was procedure text, 7) Palembang local culture reading materials were not readily accessible. 8) The purpose of including Palembang culture in reading materials for students was to increase their knowledge of Palembang local cultures and improve their English proficiency in reading skills, especially in comprehension of the text. 9) The Palembang local culture aspect that the students needed was traditional foods, 10) An Android application was required to help the teaching and learning process. DIt was also required to create procedural text reading materials for supplementary with Palembang local culture using an Android application, which complemented the students' English proficiency. The application may benefit their future careers.